Cross-National Similarities and Differences between Legacy and Digital-Born News Media Audiences - Vara-Miguel, Alfonso (2020)
The decline of the news business model for print newspapers in many Western countries and the digital disruption caused by the Internet have influenced the rise of digital-born news media. These new media are different from legacy brands in terms of business models, distribution strategies, corporate organisation, and editorial priorities. It would be expected that the different nature of both legacy and digital-born news media has driven to two types of significantly different audiences. This article aims to analyse whether there are significant differences between the users of these two types of media, by comparing the online audiences of five European countries’ (United Kingdom, Germany, France, Spain, and Italy) legacy and digital-born media brands in 2015 and 2019. The article will focus on four aspects: demographic and socioeconomics profiles (sex, age, income and level of education); interest in news; payment for online news; and media trust.